Characterization of chemical composition and particle size distribution of aerosols released during laser cutting of fuel debris simulants. Issue 4 (August 2020) - Dazon, C.; Porcheron, E.; Journeau, C.; Suteau, C.; Chagnot, C.; Doyen, I.; Excoffier, E.; Roulet, D.
Graphical abstract: Highlights: Original data on the characterization of surrogate radioactive airborne particles. Smaller particles have non negligible radioactivity. Improvement perspectives for dismantling applications stem from the results. Abstract: We present here the results regarding the characterization of chemical composition and size distribution of aerosols released during laser cutting of two types of fuel debris simulants (Ex-Vessel and In-Vessel scenarios) in air and underwater conditions in the context of Fukushima Daiichi dismantling. The aerosols have systematically an aerodynamic mass median diameter below 1 μm, with particle sizes generally comprised between 60 nm and 160 nm for air cutting conditions, and larger diameters (300−400 nm) for underwater experiments. Regarding the chemical composition, iron, chromium and nickel are mainly found by more than 50 % in the samples whereas radioactive surrogates of Uranium (Hafnium) are undetectable. When compositions are transposed to radioactivity, taking into account radioisotope inventories 10 years after the accident, it is well evidenced that the radioactivity is carried out by small particles in air condition tests (median size around 100 nm) than underwater (median size around 400 nm): 50 % of the radioactivity is present in particles below 90 nm, and 99 % below 950 nm. Caesium carries the largest part of the radioactivity at all sizes below 1 μm in the case of an Ex-Vessel fuel debris simulant. For the In-Vessel, the aerosol median size for the radioactivity is situated around 100 nm, with 59 % of the radioactivity is carried by strontium, 17 % by barium and 16 % by minor actinides (modelled by cerium) and 7% by the caesium. For sizes above 1.6 μm, cerium representing alpha particles (surrogate of plutonium) is almost the only radioactivity-bearing element (96–97 % of the radioactivity). The data produced here could already be used for modelling or designing development of strategies to implement in-situ the laser cutting for fuel debris retrieval and safety associated strategies.